The Application of the Numbered Heads Together (NHT) Cooperative Learning Model to Improve Memory in Learning Degree of Comparison among Grade XI-C1 Students at SMAN 2 Pamekasan - Hanadi Putri; Khodatul Jannah; Lukluk Ibana; Dinar Vincy Yunitaka B; Laily Laily (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This classroom action research aims to improve students' memory in learning the